ANALISIS KUALITAS SOAL PILIHAN GANDA DALAM ASESMEN SUMATIF MATEMATIKA MENGGUNAKAN TEORI TES KLASIK - Annisa Nur Azizah; Fuad Luky Atmaja (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
The purpose of this study is to describe the quality of objective test items used in summative assessments for mathematics based on classical test theory. This study will examine the aspects of difficulty, discriminative power, and the effectiveness of distractor options. The method used in this study is a descriptive quantitative approach involving 57 students from classes VIII A1 and VIII B as participants. The data used in this study were taken from 25 multiple-choice items on the summative assessment for the first semester of the 2025/2026 academic year, which were then analyzed using Microsoft Excel. The analysis results showed that the majority of items (56%) fell into the “moderate difficulty” category, while 40% were categorized as easy and 4% as difficult. In terms of discriminative power, 56% of the items fell into the “good to very good” category; meanwhile, 16% of the items were found to have low discriminative power. The effectiveness of distractors indicated that 70.67% of distractors functioned effectively, and 80% of the exam questions had good to very good distractor quality. Overall, this assessment tool is of good quality; however, some questions need to be revised to ensure more accurate and appropriate measurement of student skills.”